Un-tying Patriarchal Legacy: Polygamy in the Indonesian Novel 'Entrok' - Shofah, Novia Adibatus; Indriyani, Jiphie Gilia; Atikurrahman, Moh (Pusat Studi Gender Universitas Jember, 2026)
This article examines how Entrok, a novel by Okky Madasari, portrays the oppressive realities of polygamy and patriarchal domination within Indonesia’s socio-political landscape, especially during the New Order regime. Using feminist literary criticism as the main theoretical framework, supported by a Marxist view on economic power, this study explores how literature critically reflects women’s lived experiences under systemic gender inequality. While previous studies have discussed gender bias and resistance in Entrok, few have examined polygamy as a tool of patriarchy or analysed how resistance strategies vary across women’s social and educational positions. The analysis reveals a clear contrast in how female characters respond to polygamy and patriarchal structures. Yu Yem, Yu Parti, Endang Sulastri, and Marni, who represent uneducated women, not only reject and do not tolerate polygamy but also actively resist it by building economic independence, thus asserting their agency and autonomy. Their refusal becomes a form of open defiance against patriarchal expectations. Conversely, Rahayu, an educated woman, accepts her position as a second wife under religious justification, internalising patriarchal norms despite experiencing profound psychological distress. These representations demonstrate how both class and ideology influence women's capacity and methods of resistance to gendered oppression. Framing Entrok within broader feminist and socio-political discourse, this study affirms the novel’s role as a critique of patriarchal injustice. It underscores how fiction can challenge ideological violence and support Sustainable Development Goal 5 on Gender Equality by imagining alternative possibilities for empowerment and resistance.